2021
DOI: 10.1038/s41598-021-82858-1
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrition of Gaur (Bos gaurus C.H. Smith, 1827) at the edge of Khao Yai National Park, Thailand

Abstract: The presence of gaur (Bos gaurus) at the border of Khao Yai National Park (KYNP) in Thailand has resulted in a dramatic increase in the number of individuals’ crop feeding. This study examines the feeding adaptations of gaur at the edge of the protected area and assesses whether gaur response to increased nutrient availability in crop plants compared to natural forage. During the day, gaur mostly utilized forest areas in KYNP and entered the agricultural areas at night. Gaur ate 43 natural forage species. Natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…The CP content of open forest is significantly less than that of closed forest, because the biomass is less. Open habitat management is more efficient than closed habitat management (Chaiyarat et al, 2021;Frank et al, 2016;Ofstad et al, 2016;Tschöpe et al, 2011). Suggested pilot area optimal for tiger prey species are shown in Figure 8.…”
Section: Integrated Habitat Management; Habitat Suitability and Forag...mentioning
confidence: 99%
“…The CP content of open forest is significantly less than that of closed forest, because the biomass is less. Open habitat management is more efficient than closed habitat management (Chaiyarat et al, 2021;Frank et al, 2016;Ofstad et al, 2016;Tschöpe et al, 2011). Suggested pilot area optimal for tiger prey species are shown in Figure 8.…”
Section: Integrated Habitat Management; Habitat Suitability and Forag...mentioning
confidence: 99%
“…Agriculture showed the least suitability with only 0.08 probability of presence. Gaur utilize agricultural fringes mostly at night to feed and leave to adjacent secondary forest habitat early morning to avoid conflict (Chaiyarat et al, 2021). Gaur are generally shy and avoid contact as much as possible (Ahrestani, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of Siam weed by large herbivores is unclear. While some authors suggested potential toxicity of Siam weed leaves for consumers (Sajise et al ., 1974; Aterrado & Talatala‐Sanico, 1988), it makes a substantial part of the gaur Bos gaurus diet (Chaiyarat, Prasopsin, & Bhumpakphan, 2021). Unlike its consumption, evidence for the avoidance of heavily invaded habitats by large herbivores is clearer.…”
Section: Discussionmentioning
confidence: 99%